A Pilot Survey on Quality Control and Method Evaluation Practices in Clinical Laboratories in Nepal - Pant, Vivek; Loh, Tze Ping; Pradhan, Santosh; Gautam, Keyoor; Pyakurel, Devish (EJIFCC, 2024)
There is a lack of systematic collection of information on the quality control practice and method evaluation approach in clinical laboratories in Nepal. Such data is important to formulate educational activities and policy that may address any potential knowledge and practice gap identified. The pilot survey included twelve questions regarding quality control practice and method evaluation approach and was distributed among the laboratory medicine professionals in Kathmandu, Nepal. Data were collected using a structured self-reported questionnaire on the Google Docs platform. A total of 43 responses were received. Internal quality control and method evaluation practice varied considerably in terms of the number of levels of material used, frequency of analysis, type and source of material and acceptance criteria among responding laboratories. The variability in quality control practice and method evaluation approach highlights need for augmentation of knowledge, attitude, and practice behavior among laboratory professionals in Nepal.